ReliefP, an automated bedsore prevention device, primary benchtop evaluation - Tauheed, Abu Saquib; P., Ranjith; Kakani, Vimal K.; Shetty, Sujay (International Journal Of Community Medicine And Public Health, 2022)
Background: Few disease states ever present themselves to an attainable and near-term solution as pressure ulcers. Bedsore develops when blood supply to the skin is cut off for more than 2 to 3 hours. As the skin dries, bedsore first starts as a red, painful area, which eventually turns purple. Left untreated, skin can break open and the area can become infected. Method: A set of 50 subjects were identified who are willingly volunteering in the test. As the COVID-19 pandemic has extensively limited access to the hospital and patients, it was decided to conduct the experiment in-house. Results: For all the 50 volunteers, the device was able to relieve the high-pressure point under the patient heel within 20 mins. The mean time taken is 11 mins 6 sec. Conclusions: This preliminary study provides some initial data supporting the hypothesis that the RelifP device can identify and relieve the high-pressure area and equalize the pressure throughout. This technology can positively impact prevention in bedsores and reduce the pain and distress borne by the affected patient and caregivers.